2017
DOI: 10.1038/nature22063
|View full text |Cite
|
Sign up to set email alerts
|

Cohesin is positioned in mammalian genomes by transcription, CTCF and Wapl

Abstract: Mammalian genomes are spatially organized by CCCTC-binding factor (CTCF) and cohesin into chromatin loops and topologically associated domains, which have important roles in gene regulation and recombination. By binding to specific sequences, CTCF defines contact points for cohesin-mediated long-range chromosomal cis-interactions. Cohesin is also present at these sites, but has been proposed to be loaded onto DNA elsewhere and to extrude chromatin loops until it encounters CTCF bound to DNA. How cohesin is rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

57
473
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 422 publications
(558 citation statements)
references
References 48 publications
(76 reference statements)
57
473
6
1
Order By: Relevance
“…Cohesin promotes the extrusion of chromatin loops until it encounters CTCF bound to DNA (Merkenschlager and Nora, 2016). While CTCF binds specific DNA sequences, recent evidence indicates that transcription significantly contributes to positioning cohesin in the mammalian genome (Busslinger et al, 2017). Here we showed that the Rroid locus and Id2 promoter interact with each other through a long-range chromatin loop.…”
Section: Discussionmentioning
confidence: 99%
“…Cohesin promotes the extrusion of chromatin loops until it encounters CTCF bound to DNA (Merkenschlager and Nora, 2016). While CTCF binds specific DNA sequences, recent evidence indicates that transcription significantly contributes to positioning cohesin in the mammalian genome (Busslinger et al, 2017). Here we showed that the Rroid locus and Id2 promoter interact with each other through a long-range chromatin loop.…”
Section: Discussionmentioning
confidence: 99%
“…These differences are likely caused at least in part by the fact that DT40 and U2OS cells are dividing cells, and cohesin spends less time on chromatin before its removal by separase. We conclude that distinct model systems lead to differently appearing chromosome territories, the morphology of which may also vary based on the cohesin subunit that is analyzed (SMC3 here vs. SCC1 in previous studies) (Tedeschi et al 2013;Busslinger et al 2017;Haarhuis et al 2017).…”
Section: Esco1/2 Mediate the Organization Of Interphase Chromosome Tementioning
confidence: 99%
“…WAPL is important for the organization of cohesin-defined chromosome territories, as observed in post-mitotic MEFs and haploid human cell lines mutated in WAPL (Tedeschi et al 2013;Busslinger et al 2017;Haarhuis et al 2017). When we analyzed the pattern of cohesin staining in DT40 interphase cells (6 h after WAPL depletion) (see Fig.…”
Section: Esco1/2 Mediate the Organization Of Interphase Chromosome Tementioning
confidence: 99%
“…Cohesin rings are composed of the core subunits SMC1, SMC3, RAD21, and STAG [58,59]. Cohesin is most likely loaded onto its chromatid substrate by the NIPBL2/Mau2 cohesin-loading complex, which is enriched at transcription start sites (TSS) [60,61]. Conversely, cohesin release from chromatids is facilitated by WAPL [62].…”
Section: Chromosome Architecture and Epigenetic Control Of Glucocortimentioning
confidence: 99%
“…Indeed, while inhibiting cohesin loading (by inhibiting cohesin loading factors) inhibits the formation of topologically associated domains, inhibiting cohesin release by inhibiting WAPL restricts loop extension [64]. In the absence of both CTCF and WAPL, cohesin accumulates in up to 70 kilobase-long regions at the 3â€Č-ends of active genes, in particular, if these converge on each other [60,61].…”
Section: Chromosome Architecture and Epigenetic Control Of Glucocortimentioning
confidence: 99%